Incidence Rates for Tuberculosis Among HIV Infected Patients in Northern Tanzania - Mollel, Edson W.; Maokola, Werner; Todd, Jim; Msuya, Sia E.; Mahande, Michael J. (Frontiers in Public Health, 2019)
Background: HIV and tuberculosis (TB) are leading infectious diseases, with a high risk of co-infection. The risk of TB in people living with HIV (PLHIV) is high soon after sero-conversion and continues to increase with depletion of CD4 count Methodology: We used routinely collected data from Care and Treatment Clinics (CTC) in three regions in northern Tanzania. All PLHIV attending CTC between January 2012 to December 2017 were included in the analysis. TB incidence was defined as cases started on anti-TB medications divided by the person-years of follow-up. Poisson regression with frailty models were used to determine incidence rate ratios (IRR) and 95% confidence intervals (95%CI) for predictors of TB incidences among HIV positive patients. Results: Among 78,748 PLHIV 405 of patients developed TB over 195,296 person-years of follow-up, giving an overall TB incidence rate of 2.08 per 1000 person-years. There was an increased risk of TB incidence, 3.35 per 1000 person-years, in hospitals compared to lower level health facilities. Compared to CD4 counts of less than 350 cells/ul, higher CD4 count was associated with lower TB incidence, 81% lower for CD4 count of 350-500 cells/ul (IRR 0.19, 95%CI 0.04-0.08) and 85% lower for those with CD4 count above 500 cells/ul (IRR 0.15,95%CI 0.04-0.64). Independently, those taking ART had 66% lower TB incidences (IRR 0.34,95% CI0.15-0.79) compared to those not taking ART. Poor nutritional status and CTC enrollment between 2008 and 2012 were associated with higher TB incidences (IRR 9.27, 95% CI 2.15-39.95) and (IRR 2.97, 95% CI 1.05-8.43) respectively. Discussion: There has been a decline in TB incidence since 2012, with exception of the year 2017 whereby there was higher TB incidence probably due to increased roll out of Genexpert MTB/RIF. Among HIV positive patients attending CTC, poor nutritional status, low CD4 counts and not taking ART treatment were associated with higher TB incidence, highlighting the need to get PLHIV on treatment early, and the need for close monitoring of CD4 counts. Data from routinely collected and available health services can be used to provide evidence of epidemiological risk of TB.